Inconsistent Time-Dependent Effects of Tetramethylpyrazine on Primary Neurological Disorders and Psychiatric Comorbidities - Jiang, Yue-Peng; Jin, Yan; Bao, Jie; Wang, Song; Lai, Wei-Dong; Wen, Cheng-Ping; Xu, Zheng-Hao; Yu, Jie (Frontiers in Pharmacology, 2021)
The aim of this study was to investigate the time dependent effects of tetramethylpyrazine (TMP, main activity compound of Ligusticum chuanxiong Hort) on two neurological disorders and their neuropsychiatric comorbidities. 6 Hz corneal rapid kindling was used to induce epileptogenesis and the inflammatory pain was induced by intra-articular CFA (Complete Freund's adjuvant) injection. The mechanical pain thresholds were measured using von Frey hair (D4, D11, D18, D25 after CFA first injection), and the vertical rearings of the mice was observed. To test the neuropsychiatric comorbidities, anxiety-like behaviors of mice were examined by open field and elevated plus maze tests. Two behavioral despair models, tail suspension test and forced swimming test were also used to evaluate the depressive like behaviors. The results showed that TMP administered from the initial day (D1-D35 in kindling model, D0-D14 and D0-D28 in CFA model) of modeling retarded both the developments of 6 Hz corneal rapid kindling epileptogenesis and the CFA induced inflammatory pain. In comparison, late periods administration of TMP (D21-D35 in kindling and D14-D28 in CFA model) showed no effect on the epileptogenesis and the generalized seizures (GS) of kindling, but alleviated maintenance of CFA induced inflammatory pain. Furthermore, we also found all TMP treatments from the initial day of modeling alleviated the co-morbid depressive and anxiety-like behaviors in both models; however, late periods treatments did not, either in kindling or the CFA induced inflammatory pain. BDNF/ERK signaling impairment was also tested by western blot, and the results showed that TMP administered from the initial day of modeling increased the hippocampal BDNF/ERK expression, whereas late period administration showed no effects. Overall, our findings reveal the inconsistent time dependent effects of Tetramethylpyrazine on neurological disorders and their relative neuropsychiatric comorbidities, and provide novel insight into the early application of TMP that might enhance hippocampal BDNF/ERK signaling to alleviate neuropsychiatric comorbidities in neurological diseases.